Development of innovative financial products in Europe: Case of exchange-traded products in Germany - Adam Marszk (Institute of Economic Research (IER), 2017)
Research background: Exchange-traded products (ETPs) are one of the most rapidly growing categories of financial products. Their fast development has been boosted by innovative features. Three main categories of ETPs are exchange-traded funds (ETFs), exchange-traded commodities (ETCs) and exchange-traded notes (ETNs). ETCs and ETNs remain least known, even though their number on some stock exchanges is high. In Europe, Germany is one of the largest and most active ETPs markets. ETCs and ETNs are debt instruments, in contrast with the most popular ETFs, which are equity securities. Therefore, they offer investors different advantages but also expose them to other types of risks. Purpose of the article: The key aim of the article is to present the features of ETPs and to provide in-depth insight into the issues linked with the development of ETPs market in Germany, with the special emphasis on the ETCs and ETNs. Methodology/methods: German ETPs market is analyzed using descriptive statis-tics and technological substitution framework (employed for the analysis of inno-vations in order to evaluate the changing market shares of ETFs, ETCs and ETNs). Main period of the analysis is 2010-2016 and monthly data are used. Findings: Share of ETPs other than ETFs in the total market in Germany remains low. Even though market position of the leading products, i.e. ETFs, is still very strong, some substitution has been observed, especially after 2015. Predictions made using technological substitution model indicate that this trend (growing mar-ket share of ETCs and ETNs) will continue in the upcoming years.
Keywords: G11; G12; G23; O16; 330; exchange-traded funds; exchange-traded products; financial innova-tions; stock exchange; Germany